2021
DOI: 10.1186/s43141-020-00111-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of correlation between asthenozoospermia and mitochondrial DNA mutations in Egyptian infertile men

Abstract: Background Asthenozoospermia is a chief reason for male seminal pathologies with an impression of around 19% of infertile patients. Spermatozoa mitochondrial DNA variations seem to link with low sperm motility. The objective of the study was to assess the relation between mitochondrial mutations and male sterility, especially in asthenozoospermia. The patient semen samples were investigated by studying the sperm physical characters; motility, viability, and morphological parameters were then cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
4
9
0
Order By: Relevance
“…The rs2001031 (A8860G) and rs2000975 (A8701) were reported by a current study in which they were found to make a change in the amino acid sequence from threonine to Alanine and they were signi cantly associated with asthenozoospermia. In this study, we have reported the same SNPs but statistically, they were not calculated as signi cant variations although they both cause a missense variation in the coding portion (Abd Elrahman et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The rs2001031 (A8860G) and rs2000975 (A8701) were reported by a current study in which they were found to make a change in the amino acid sequence from threonine to Alanine and they were signi cantly associated with asthenozoospermia. In this study, we have reported the same SNPs but statistically, they were not calculated as signi cant variations although they both cause a missense variation in the coding portion (Abd Elrahman et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Reactive oxygen species (ROS) are byproducts of the mitochondrial respiratory chain, the mutation rate generated by ROS is 10-100 times greater than nuclear DNA because the mitochondrial DNA is located in the mitochondrial matrix (Shamsi et al, 2008). The mammalian sperm consists of about 22 to 75 mitochondria located in the midpiece of the sperm, ensuring proper function of the agella and normal sperm motility for an e cient fertilization process (Abd Elrahman et al, 2021). Therefore, any genetic alteration of this limited number of mitochondria can be related to the improper function of the sperm.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed five non-synonymous SNPs in nicotinamide adenine dinucleotide hydrogen (NADH) dehydrogenase 1 gene (ND1) located at nucleotides T3398C, T3821C, G4048A, T4169TT, and T4216C. Since secondary structure prediction of T3398C and T3821C proteins revealed a negative change in protein function, these alterations could result in sperm motility decline and male infertility [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors involved in male infertility manifest as chromosomal disorders, mitochondrial DNA (mtDNA) mutations, monogenic disorders, multifactorial disorders, and endocrine disorders of genetic origin. Male infertility is often related to chromosome abnormalities or other genetic factors (Holyoake et al 2002;Nakada et al 2006; Elrahman et al 2021;Thomas et al 2021). DNAH6 (Dynein Axonemal Heavy Chain 6) is a protein-coding gene, part of the microtubule-associated motor protein and is a testis-speci c-expressed protein, located in the neck region of the spermatozoa, required for the function of cilia function in spermatozoa (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%